1998
DOI: 10.1002/elps.1150190305
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a mixture of charged and neutral additives on analyte migration behavior in capillary electrophoresis

Abstract: Multicomponent additives, such as derivatized cyclodextrins with various degrees of substitution, can be considered single-component additives as long as the fraction of each component remains constant. In this paper, equations are derived describing the effect of such additives on the migration behavior of analytes. These equations are used in the study of capillary electrophoresis (CE) systems with differentially charged cyclodextrins as additives. For weakly acidic analytes, the binding with highly negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Thus, experimental effective mobilities should be corrected for viscosity, temperature and ionic strength variations, which depend on variations of the chiral selector concentration and ionic strength. These corrections are crucial for an accurate determination of binding parameters [53].…”
Section: Estimation Of T Complexation Constant and Complex Mobilitymentioning
confidence: 99%
“…Thus, experimental effective mobilities should be corrected for viscosity, temperature and ionic strength variations, which depend on variations of the chiral selector concentration and ionic strength. These corrections are crucial for an accurate determination of binding parameters [53].…”
Section: Estimation Of T Complexation Constant and Complex Mobilitymentioning
confidence: 99%
“…As discussed in the Migration section, this is consistent with the theoretical development demonstrating that multicomponent additives in CE act as a weighted average of equilibrium and mobility behavior, and so can be treated as a single component if the relative amount of each component is constant. 35 Thus, the simple presence of different additives with different charges does not itself lead to variations in mobility and decreased separation robustness. However, if there is significant lot-to-lot variation for these random CDs that alters the fraction of each component in the mixture, then significant mobility variations can be expected between lots.…”
Section: Separation Robustnessmentioning
confidence: 99%
“…2 is a weighted average of the selector species present. 35 Analyte mobility, in this case, is a weighted average of the fraction of each selector species present. 35 If the relative composition of the mixture remains constant, Eq.…”
Section: Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…This equation has then become a basis for further method optimization in the dual-selector systems, predominantly in enantioseparations [25]. Similarly to the pH-overall model, Kranack et al [26] and later us [27] have shown that, effective mobility of an analyte (present in a single free form) interacting with a mixture of selectors can be expressed in a form of the S A S S Eq. (4):…”
Section: Introductionmentioning
confidence: 98%